Perbedaan Warna Kontainer Berkaitan dengan Keberadaan Jentik Aedes aegypti di Sekolah Dasar - Budiyanto, Anif (Central Basic Biomedical and Health Technology, 2012)
Containers inside and outside the school building are breeding places for Dengue vector. Presence or absence of Ae aegypti mosquito larvae in a container could be affected by the type, location, color, material, condition and volume of container lid. The purpose of this study was to determine the condition of container that affect the presence of Ae aegypti mosquito larvae. A cross sectional survey was conducted to collect mosquito larvae in primary schools in the district of Ogan Komering Ulu, South Sumatera Province with a single larvae method. Mosquito larvae were found in 54% of surveyed-schools (54%), and mostly were Aedes aegypti larvae (91%). There was a significant correlation between dark and light color differences of the water container in the presence of mosquito larvae (P value = 0.017, CI 95% = 1.2 to 2.9). On the other hand, there was no significant correlation between different types of containers, location of containers, material of containers, the container lid and the volume of water in a container in the presence of larvae. There was a significant correlation between the difference in containerâs color (light and dark) in the presence of Ae aegypti mosquito larvae. It is recommended to have regular cleaning of the containers in order to prevent dirt or mosses covered the containers which will impress of being dark color.Key words: dengue, Aedes aegypti, larvae, containers, school.Â AbstrakKontainer bagian dalam dan luar sekolah menjadi tempat perindukan vektor Dengue. Ada tidaknya larva Aedes aegypti didalam kontainer dapat dipengaruhi oleh tipe, lokasi, warna, material kondisi dan volume dari kontainer. Tujuan dari penelitian ini untuk menentukan kondisi kontainer yang dapat mempengaruhi adanya larva Aedes aegypti. Penelitian ini adalah survey Cross seksional yang dilakukan dengan mengumpulkan larva nyamuk di sekolah dasar di Kabupaten Ogan Komering Ulu di Sumatera Selatan dengan metode larva tunggal. Larva nyamuk ditemukan pada 54% sekolah yang di survey, dan terutama adalah larva Aedes aegypti (91%). Tedapat korelasi signifikan adanya larva nyamuk diantara kontainer yang berwarna gelap dan terang (P value = 0,017, CI 95% = 1,2-2,9). pada sisi lain ditemukan korelasi yang tidak signifikan antara tipe, lokasi, material, ukuran dan volume air dalam kontainer terhadap keberadaan larva .Terdapat korelasi yang signifikan antara kontainer yang berwarna gelap dan terang dan keberadaan larva nyamuk Aedes aegypti. Direkomendasikan untuk selalu membersihkan kontainer supaya kontainer tidak memberikan warna gelap.Kata kunci: dengue Aedes aegyti, larva, container, sekolah